Integration of technology and Pancasila-based civic education in strengthening students’ character in Medan senior high schools - Kesuma, Sapta; Susilawati, Evi; Tanjung, Juliansyah Putra; Fadhilah, Cut Rafiqa; Admiral, Raden Deni; Mardiansyah, Mardiansyah; Lubis, Halimah Tussadiah; Nasution, Ila Rahmayati; Purnomo, Tjong Adrian; Harahap, Evi Syuriani (Edelweiss Applied Science and Technology, 2025)
The digital era presents new challenges to education, particularly the rise of negative behaviors among adolescents, such as violence, intolerance, and social deviance. This issue has also emerged among high school students in Medan, Indonesia, characterized by declining discipline and moral awareness due to uncontrolled digital media exposure. This study aims to analyze the integration of technology within Pancasila-based Civic Education as a strategic effort to prevent negative behaviors. A quantitative approach using multiple linear regression was employed to examine the effects of learning technology integration, internalization of Pancasila values, and digital environmental conditions on student behavior. Data were obtained from structured questionnaires distributed to students from public and private high schools in Medan. Results reveal that integrating technology into Civic Education significantly enhances students’ moral awareness and digital ethics. The application of Pancasila values through digital Project-Based Learning (PjBL) effectively reduces aggression, intolerance, and unethical social media behavior. Moreover, a regulated digital environment and teachers’ proactive moral guidance contribute greatly to character formation. The study emphasizes the synergy between Pancasila-based value education and digital transformation in shaping ethical and civically responsible youth.